The Effects of Unemployment, Education, and Investment on Poverty in Java-Bali - Kurniawan, Heru (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Poverty is a crucial problem faced by almost all countries in the world including Indonesia, many studies show that education and investment are the solutions to poverty while unemployment is the source of poverty. This paper aims to see if there is an effect of education, investment and unemployment on poverty on the islands of Java and Bali. this research uses quantitative methods with Ordinary Last Square (OLS) techniques, the type of data used is panel and the data source used is secondary data obtained from BPS Each province in Java and Bali. the results of this study indicate that poverty can be overcome by education, and opening employment through labor-intensive investment which results in economic growth on the island of Java and Bali. unemployment can increase poverty if the investment is not on target. To balance the investment that continues to increase every year, the education aspect needs to be considered, education will improve the welfare of the community through increased income and decent wages. Investment needs to be balanced with the quality of human resources so that welfare can reach various regions in Java and Bali.